2010
DOI: 10.1007/s10763-010-9248-x
|View full text |Cite
|
Sign up to set email alerts
|

First Year Implementation of a Project-Based Learning Approach: The Need for Addressing Teachers’ Orientations in the Era of Reform

Abstract: The purpose of this study was to examine the extent to which three teachers' professional experience and existing orientations toward teaching and learning mathematics and science influenced their implementation of a project-based curriculum (i.e. project-based learning (PBL)). Data sources included interviews, videotapes of classroom activity, and a teaching philosophy questionnaire. Data analysis was conducted using an iterative coding technique. We found coherency between the teachers' perceived orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 25 publications
4
55
0
5
Order By: Relevance
“…2 (Fall 2013) Several studies reported results on how teachers begin to use PjBL after they have been exposed to it through professional development. Most of these studies showed that teachers struggled when trying to implement PjBL in the classroom even after being energized and enthusiastic about it during the training (Ravitz, 2003;Ravitz et al, 2004;Park Rogers et al, 2010;Vratulis et al, 2011). In fact, Levine et al (2010) specifically pointed at the struggle in playing the new role required by teachers in PjBl, the struggle in managing the project environment, in scaffolding, and in assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (Fall 2013) Several studies reported results on how teachers begin to use PjBL after they have been exposed to it through professional development. Most of these studies showed that teachers struggled when trying to implement PjBL in the classroom even after being energized and enthusiastic about it during the training (Ravitz, 2003;Ravitz et al, 2004;Park Rogers et al, 2010;Vratulis et al, 2011). In fact, Levine et al (2010) specifically pointed at the struggle in playing the new role required by teachers in PjBl, the struggle in managing the project environment, in scaffolding, and in assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted the need for teachers to understand how to shift to more student-centered approaches and how to adopt new instructional pedagogies to grade levels and classroom contexts. Exploring how three teachers implemented PjBL for the first year, Park Rogers, Cross, Gresalfi, Trauth-Nare, and Buck (2010) reported that teachers had different views on their roles, different views on the compatibility of PjBL with their views on teaching and learning, and difficulties in helping students "adjust to a new style of learning" (p.905). They asserted that teachers' orientation and past professional experience affect the degree to which they implemented PjBL, and that teachers needed guidance on what instructional strategies to use to support the implementation of PjBL.…”
Section: Adopting New Instructional Strategiesmentioning
confidence: 99%
“…In 33 articles (for example, [1,4,5,11,12,19,29,[43][44][45]), the authors provided a definition of PBSTL, 6 either in a clearly identified section (25 articles) or indirectly throughout the text (8 articles). In 15 texts, the authors did not provide a definition for this approach (for example, [6][7][8][9]14,15,18,39]). …”
Section: The Concepts and Features Used To Define Them (Q1)mentioning
confidence: 99%
“…Others emphasise an attribute in their definitions because, for them, PBSTL provides a mean for promoting it: the active engagement of students in learning and knowledge construction (e.g. [20,22,25,35,39,43]). The two quotes below illustrate these definitions; others are provided in Supplementary material 2:…”
Section: Pbstl Is In Keeping With Constructivist and Socioconstructivmentioning
confidence: 99%
“…One of the goals of school mathematics learning is the ability to solve problems (Goodnough & Hung, 2008;MOEC, 2016;Putra, Herman, & Sumarmo, 2017). Therefore, problem solving has become an important focus in school mathematics curriculum started from primary school level to the high school level (Istiandaru, Istihapsari, Wardono, & Mulyono, 2015;Park Rogers, Cross, Gresalfi, Trauth-Nare, & Buck, 2011).…”
Section: Introductionmentioning
confidence: 99%